2016
DOI: 10.1002/rcm.7496
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of compound‐specific carbon isotope ratios (δ13C values) via direct injection of whole crude oil samples

Abstract: RATIONALE: Stable isotope analysis is a powerful tool in understanding the generation, history and correlation of hydrocarbons. Compound-specific δ 13 C measurements of oils allow detailed comparison of individual compound groupings; however, most studies of these sample materials separate and isolate individual fractions based on the chemistries of particular compound groups, potentially losing considerable valuable isotopic data. Even if all fractions are analyzed, this represents a large increase in the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Crude oil is mainly composed of carbon and hydrogen, with very little nitrogen, which would have resulted in much higher TOC/TN ratios, compared to marine and terrigenous organic matter, if a significant fraction remained. Previous studies showed that d 13 C of crude oil normally range from À32 to À24‰ (Wang et al, 2013b;Barrie et al, 2016;Muhammad et al, 2017). The ranges and mean values of TOC/TN and d 13 C in our study indicated the presence of impacts from oil.…”
Section: Toc Toc/tn and D 13 Csupporting
confidence: 62%
“…Crude oil is mainly composed of carbon and hydrogen, with very little nitrogen, which would have resulted in much higher TOC/TN ratios, compared to marine and terrigenous organic matter, if a significant fraction remained. Previous studies showed that d 13 C of crude oil normally range from À32 to À24‰ (Wang et al, 2013b;Barrie et al, 2016;Muhammad et al, 2017). The ranges and mean values of TOC/TN and d 13 C in our study indicated the presence of impacts from oil.…”
Section: Toc Toc/tn and D 13 Csupporting
confidence: 62%
“…The δ 13 C values of Pr and Ph determined directly from the whole oil and/or the saturated fraction were consistent with those from the branched/cyclic alkane fraction, with an RSD of less than 0.43%. The accuracy and precision were acceptable [10, 12].…”
Section: Resultsmentioning
confidence: 99%
“…Compound‐specific carbon and hydrogen isotopic ratios of individual organic compounds can be determined by compound‐specific isotope analysis (CSIA) using GC with isotope ratio mass spectrometry (IRMS). Reviews and multiple research papers have documented detailed information on analytical methods and the use of compound‐specific carbon and hydrogen isotopic data [9–12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations